Rhodnius prolixus interaction with Trypanosoma rangeli: modulation of the immune system and microbiota population - Cecilia S Vieira; Débora P Mattos; Peter J Waniek; Jayme M Santangelo; Marcela B Figueiredo; Marcia Gumiel; Fabio F da Mota; Daniele P Castro; Eloi S Garcia; Patrícia Azambuja (Parasites & Vectors, 2015)
Abstract Background Trypanosoma rangeli is a protozoan that infects a variety of mammalian hosts, including humans. Its main insect vector is Rhodnius prolixus and is found in several Latin American countries. The R. prolixus vector competence depends on the T. rangeli strain and the molecular interactions, as well as the insect’s immune responses in the gut and haemocoel. This work focuses on the modulation of the humoral immune responses of the midgut of R. prolixus infected with T. rangeli Macias strain, considering the influence of the parasite on the intestinal microbiota. Methods The population density of T. rangeli Macias strain was analysed in different R. prolixus midgut compartments in long and short-term experiments. Cultivable and non-cultivable midgut bacteria were investigated by colony forming unit (CFU) assays and by 454 pyrosequencing of the 16S rRNA gene, respectively. The modulation of R. prolixus immune responses was studied by analysis of the antimicrobial activity in vitro against different bacteria using turbidimetric tests, the abundance of mRNAs encoding antimicrobial peptides (AMPs) defensin (DefA, DefB, DefC), prolixicin (Prol) and lysozymes (LysA, LysB) by RT-PCR and analysis of the phenoloxidase (PO) activity. Results Our results showed that T. rangeli successfully colonized R. prolixus midgut altering the microbiota population and the immune responses as follows: 1 - reduced cultivable midgut bacteria; 2 - decreased the number of sequences of the Enterococcaceae but increased those of the Burkholderiaceae family; the families Nocardiaceae, Enterobacteriaceae and Mycobacteriaceae encountered in control and infected insects remained the same; 3 - enhanced midgut antibacterial activities against Serratia marcescens and Staphylococcus aureus; 4 - down-regulated LysB and Prol mRNA levels; altered DefB, DefC and LysA depending on the infection (short and long-term); 5 - decreased PO activity. Conclusion Our findings suggest that T. rangeli Macias strain modulates R. prolixus immune system and modifies the natural microbiota composition.